THE IMPORTANCE OF PARENTAL PARTICIPATION IN THE ABA INTERVENTION: LITERATURE REVIEW - Katrina Saavedra Ferreira, Isabella; Campos Soares, Renata; Evandro Brito de Leão, Rômulo (Health and Society, 2022)
Among all the developmental disorders that can affect a child, one of them is Autism or that has been standing out in recent years due to the high incidence of cases, also reflecting the need for greater scientific production to understand its paradigms. As a disorder that greatly affects the quality of life of children and their country, it requires an increasingly complex treatment approach. One of the known approaches to the treatment of autism is Applied Behavior Analysis, better known as ABA, which, in addition to a trained team, requires great participation from both countries. Therefore, the objective of this work was to analyze the results of the scientific literature on the importance of the participation of two countries in the ABA intervention. For this, an integrative literature review was carried out in the VHL and Pubmed databases, using the terms “family AND autism spectrum disorder”, applied behavioral analysis AND autism” and “applied behavioral analysis AND family” as descriptors and markers. A total of 1,865 articles were found, and after application of the Relevance Tests I and II, a sample of 9 analyzed articles was obtained. The articles address the importance of both countries in the application of the ABA method, reinforcing the needs of two non-treatment responsibilities and defining the possibilities of intervention shared with the country.